Perancangan Klem Untuk Cetakan Vertical Pouring Di Laboratorium Pengecoran Logam Politeknik Manufaktur Bandung - Mohamad Agus Solihin; Dodo Suhada; S Sukiman (UPT Laboratorium Terpadu, Universitas Diponegoro, 2021)
In the foundry laboratory at Bandung Polytechnic for Manufacturing, there is a student practicum program where the student learns several molding methods that are often used. One of these methods is a vertical pouring method. This is a one of mold method in the foundry process where the object is positioned vertically (vertically) with the inlet position either at the bottom of the object or at the top of the object. In this experiment using the vertical pouring method with direct pouring from a top. This method is usually used for objects that are plate shaped or cylindrical. The advantage of this method can control shrinkage and minimizes the mold area. In the process, where the object will be made in limited quantities, the mold is tied and buried in sand. The problems are processing time is longer than Cup and Drug molds, and wears a lot of sand. For this reason, a tool for clamping vertical molds is designed. This tool is expected to reduce use of sand, and reduce processing time. This tool is made of steel. vertical pouring method becomes more effective and efficient by using clamps